Incidence and mortality rates of lung cancer in Qingdao, China (2013‐2017). Issue 2 (25th March 2021) - Sun, Xiaohui; Xu, Xiang; Wang, Yumei; Hou, Binghui; Luo, Tingting; Meng, Di; Wang, Shaojie; Ning, Feng
Abstract: Aims: To analyze lung cancer incidence and mortality rates from 2013 to 2017 in Qingdao, Shandong Province, China. Methods: The lung cancer new cases and death data during 2013‐2017 were collected from the Qingdao Cancer Surveillance System. The crude incidence and mortality rates were calculated by residential area and gender. The annual percentage change (APC) was determined to evaluate the incidence and mortality rate trends. Results: Between 2013 and 2017, 31 653 new lung cancer cases and 24 965 deaths from lung cancer were retrieved. The age‐standardized incidence rates by Chinese standard population (ASIRC) were 42.1 per 100 000. The crude incidence rates for men and women increased from 85.2 and 46.3 per 100 000 in 2013 to 124.0 and 67.4 per 100 000 in 2017, respectively. The APCs were 7.8% for men ( P < .001) and 7.5% ( P = .027) for women. The crude mortality rates increased from 56.3 per 100 000 in 2013 to 68.0 per 100 000 in 2017. The age‐standardized mortality rates by ASIRC were 32.3 per 100 000. The APCs of mortality rates were higher in men than in women and were higher in rural than in urban areas. Age‐specific incidence and mortality rates were lower in individuals aged <40 years, increased sharply in those aged >40 years, and were the highest in 80‐year‐old individuals. Conclusion: These data show different patterns of incidence and mortality rate according to gender and resident area during 2013‐2017. Early screening and targeted prevention should be implemented to control the increased trend of lung cancer. Abstract : This study showed different patterns incidence and mortality rate in genders and resident areas during 2013–2017. Early screening and targeted prevention should be implemented to control the increased trend of lung cancer.